The Reality of Distance Education with Students having Autism Spectrum Disorder (ASD) from the Perspective of their Teachers in Saudi Arabia (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aims at identifying the reality of using of distance education by teachers of students with autism spectrum disorder from the perspective of these teachrrs and at finding out the impact of educational administration and years of experience. To achieve this goal, the descriptive approach was used, and a forty-one-item tool was prepared to measure the advantages, challenges and obstacles of using distance education with students having autism spectrum disorder. A questionnaire was applied to 203 teachers of students with autism spectrum disorder. The results of the study have shown the existence of obstacles in using distance education with the students under examination in the first place, based on the responses of samples, followed by the dimension of challenges of using distance education with students with autism spectrum disorder in the second place, and in the last place came the dimension of the positives of using distance education with students with autism spectrum disorder. There are statistically significant differences in relation to the educational administration variable in the dimensions: positives of using distance education in favor of the northern region, challenges of using distance education in favor of the southern region, obstacles to using distance education in favor of the southern region. The results have also shown the absence of statistically significant differences due to the variable of years of experience in the dimension: obstacles to the use of distance education, positives of using distance education, while the results revealed the existence of statistically significant differences in the dimension of challenges of using distance education in favor of a category of 3 to less than 6 years. Based on the results of this study, the researcher recommends the perpetuation of distance education with students having autism spectrum disorder, looking at the challenges that may limit their education process, and taking into account the obstacles that may hinder the continuity of their training during distance education.
Keywords: Distance Education; Autism Spectrum Disorder; Students with Autism Spectrum Disorder; Special Education Teachers